Preparation method and application of hexagonal Cu2S nanosheet and Cu2S-COPs heterojunction material

The Cu2S@COPs heterojunction material effectively addresses the inefficiencies of current photocatalysts by promoting electron-hole separation and fast electron transfer, achieving high photocatalytic efficiency in reducing U(VI) with a removal capacity of 1164.6 mg/g and selectivity in the presence of interfering ions.

CN119118184APending Publication Date: 2024-12-13NANCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411200908.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Current photocatalysts for reducing uranium(VI) in radioactive wastewater suffer from low light absorption utilization, few adsorption and reduction sites, and easy recombination of photogenerated electrons and holes, leading to low photocatalytic efficiency.

Method used

A Cu2S nanosheet with hexagonal morphology and a Cu2S@COPs heterojunction material prepared via click chemistry, which promotes electron-hole separation and has a wide light absorption range, band gap matching, and fast electron transfer.

Benefits of technology

The Cu2S@COPs heterojunction material achieves high photocatalytic efficiency in reducing U(VI) with a removal capacity of 1164.6 mg/g without sacrificial agents and shows selectivity in the presence of interfering ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118184A_ABST
    Figure CN119118184A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of environmental protection, and particularly relates to a preparation method and application of a hexagonal Cu2S nanosheet and a Cu2S-COPs heterojunction material. Oleylamine (OAM) and octadecene (ODE) are used as solvents, a sulfur precursor is injected into a copper precursor, and Cu2S nanosheets with hexagonal morphology are synthesized; the preparation method comprises the following steps: firstly, preparing 4, 4 '-diazido stilbene-2, 2'-disulfonic acid disodium salt tetrahydrate, and then carrying out in-situ synthesis on 2, 4, 6-tri (4-ethynylphenyl)-1, 3, 5-triazine and the 4, 4 '-diazido stilbene-2, 2'-disulfonic acid disodium salt tetrahydrate under the catalytic action of Cu2S through a click chemical reaction to obtain the covalent organic polymer heterostructure taking triazole as a connecting structure. The Cu2S (at) COPs heterojunction synthesized by the method disclosed by the invention has the advantages of wide light absorption range, band gap matching, high electron transfer rate, easiness in electron-hole separation, difficulty in compounding and the like, is high in photocatalytic reduction capacity on U (VI), high in efficiency and good in selectivity, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental protection, and in particular relates to a preparation method and application of a Cu2S nanosheet with a hexagonal morphology and a Cu2S@COPs heterojunction material. Background Art

[0002] Radioactive uranium-containing wastewater produced during mining can have adverse effects on ecosystems and human health. Through research on the existence forms of uranium, it was found that reducing highly mobile and soluble U(VI) to insoluble U(IV) is one of the most promising uranium removal strategies. Photocatalytic reduction of uranium has attracted widespread attention from researchers due to its low energy consumption and high efficiency.

[0003] In addition, single-component inorganic semiconductor catalysts have a narrow light absorption range and a large band gap, which is not conducive to the generation of photogenerated electrons. The ease of recombination of photogenerated electrons and holes is a key factor affecting the band gap of photocatalysts. Traditional heterojunctions are assembled from more than two inorganic semiconductor materials and have independent functional components, which can effectively promote the separation of photogenerated electrons and holes. However, in most all-inorganic heterojunction systems, there are disadvantages such as low light absorption utilization, few adsorption and reduction sites, and easy recombination of photogenerated electrons and holes, resulting in low photocatalytic efficiency of current all-inorganic systems.

[0004] Therefore, how to develop a new type of photocatalyst with high efficiency for reducing U(VI) is a technical problem that needs to be solved urgently by technicians in this field. Summary of the invention

[0005] In view of this, the present invention provides a preparation method and application of a hexagonal Cu2S nanosheet and a Cu2S@COPs heterojunction material.

[0006] It should be noted that the in-situ preparation of Cu2S@COPs heterojunction material by the click chemistry reaction catalyzed by Cu2S can promote the separation of photogenerated electrons and holes. The removal capacity of Cu2S@COPs heterojunction material for U(VI) reaches 1164.6 mg g without sacrificial agent. -1 , which is an effective strategy to improve the efficiency of photocatalytic reduction and has good application potential in the field of photocatalytic reduction of U(VI).

[0007] Specifically, the present invention prepares a Cu2S nanosheet material with a hexagonal morphology, which not only has the ability to photocatalytically reduce U(VI), but also the Cu2S@COPs heterojunction material prepared by a click chemistry reaction catalyzed by the Cu2S nanosheet has excellent removal ability for U(VI); in addition, the Cu2S@COPs heterojunction prepared by the invention has excellent photocatalytic activity such as a wide light absorption range, band gap matching, fast electron transfer rate and difficulty in electron-hole recombination, and has good selectivity for U(VI).

[0008] Covalent organic polymers (COPs) are functional organic components that can be combined with semiconductors. At the same time, COPs have rich and adjustable active functional sites and are good carriers for uranium adsorption and diffusion. In addition, COPs have strong visible light absorption ability and fast carrier mobility. They are sensitizers for semiconductors, and electrons can be quickly transferred between semiconductors and COPs. Copper (I)-catalyzed azide-alkyne click chemistry (CuAAC) is a commonly used organic synthesis reaction for preparing multifunctional COPs. The reaction has the advantages of mild conditions, high efficiency and strong specificity. At the same time, the 1,2,3-triazole ring obtained by cycloaddition has rigidity, aromaticity and electron acceptor ability. On this basis, the present invention prepares Cu2S@COPs heterojunction materials in situ through Cu2S-catalyzed click chemistry reaction, which can promote the separation of photogenerated electrons and holes, is an effective strategy to improve the efficiency of photocatalytic reduction, and has good application potential in the field of photocatalytic reduction.

[0009] In order to achieve the above object, the present invention adopts the following technical solution:

[0010] The first technical purpose of the present invention is to provide a method for preparing a Cu2S nanosheet material having a hexagonal morphology, comprising the following specific steps:

[0011] Copper chloride dihydrate and an organic solvent are mixed evenly and then degassed under nitrogen conditions, and stirred and heated for reaction under anaerobic conditions; tert-dodecyl mercaptan is injected when the temperature reaches 120-140°C, and then the temperature is continuously raised, and the reaction is carried out at 180-220°C for 10-30 minutes, and then ethanol is slowly injected to terminate the reaction, and then the reaction solution is centrifuged and washed, and the obtained Cu2S is resuspended in n-hexane and dried at room temperature to obtain Cu2S nanosheets.

[0012] Optionally, the molar ratio of cupric chloride dihydrate to tert-dodecyl mercaptan is 1-1.5 μmol:2-5 mL; the organic solvent is a mixed solution of oleylamine and octadecene in a volume ratio of 1:(0.5-2); and the molar ratio of the inorganic copper to the organic solvent is 1-1.5 μmol:3-10 mL.

[0013] Preferably, the amount of cupric chloride dihydrate is 1 μmol; the volume ratio of the organic solvent is a mixture of oleylamine and octadecene at 1:1; the volume of the oleylamine is 5 mL; the volume of the tert-dodecyl mercaptan is 5 mL; the centrifugal washing is dispersed with n-hexane and washed with ethanol precipitation; the centrifugal washing speed is 2000 rpm.

[0014] The second technical purpose of the present invention is to provide the application of the above-mentioned Cu2S nanosheet material with hexagonal morphology in the photocatalytic reduction of uranium nuclide.

[0015] It should be noted that the Cu2S nanosheet material with hexagonal morphology can photocatalytically reduce U(VI) to U(IV) under visible light irradiation conditions.

[0016] The third technical purpose of the present invention is to provide a Cu2S@COPs heterojunction material, in which an alkynyl monomer and an azide monomer are in situ synthesized into a covalent organic polymer heterostructure with triazole as a connecting structure through a click chemistry reaction under the catalytic action of Cu2S prepared by the method as claimed in claim 1.

[0017] Optionally, the alkynyl monomer is 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, and the azide monomer is disodium 4,4'-bisazidostilbene-2,2'-disulfonic acid tetrahydrate.

[0018] The fourth technical objective of the present invention is to provide a method for preparing the above-mentioned Cu2S@COPs heterojunction material, comprising the following specific steps:

[0019] The obtained Cu2S nanosheets, alkynyl monomers, azide monomers and solvents are mixed evenly, the obtained reaction solution is reacted at 70-120°C for 12-24h under stirring conditions, the solid is collected by cooling, and the Cu2S@COPs heterojunction material is obtained after centrifugal washing and drying.

[0020] Optionally, the molar ratio of the alkynyl monomer, the azide monomer, the Cu2S nanosheets and the solvent is (0.06-0.3 μmol): (0.1-0.5 μmol): (40-60 mg): (70-80 mL); the solvent is a mixture of water / dimethyl sulfoxide in a volume ratio of 1: (5-15).

[0021] Optionally, the centrifugal washing is performed with acetone, methanol and dichloromethane in sequence; the centrifugal washing speed is 5000 rpm.

[0022] The fifth technical purpose of the present invention is to provide the application of the above-mentioned Cu2S@COPs heterojunction material in the photocatalytic reduction of uranium nuclides.

[0023] It should be noted that the Cu2S@COPs heterojunction material can photocatalytically reduce U(VI) to U(IV) under visible light irradiation conditions.

[0024] Furthermore, the Cu2S@COPs heterojunction material can selectively remove U(VI) in the presence of multiple interfering ions; the multiple interfering ions include Mg(II), Al(III), Ca(II), Co(II), Ni(II), Y(III), La(III), Ce(III), Pr(III), Nd(III), Sm(III), Eu(III), Gd(III), Tb(III), Dy(III), Ho(III), Er(III), Tm(III) and Lu(III).

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The synthesis method of the Cu2S nanosheet material prepared by the present invention is simple, the reaction is rapid, and the product purity is high.

[0027] (2) The Cu2S nanosheet material prepared by the present invention has a photocatalytic removal effect on U(VI).

[0028] (3) The synthesis method of the Cu2S@COPs heterojunction material prepared by the present invention is simple and the product purity is high.

[0029] (4) The Cu2S@COPs heterojunction material prepared by the present invention has excellent photocatalytic activity such as a wide light absorption range, band gap matching, fast electron transfer rate and difficulty in electron-hole recombination, and has high efficiency in photocatalytic reduction of U(VI).

[0030] (5) In the Cu2S@COPs heterojunction material prepared by the present invention, Cu2S and COPs construct a heterostructure in situ, with a large contact area, and electrons can be quickly transferred from COPs to Cu2S, forming a high-speed charge transfer.

[0031] (6) The Cu2S@COPs heterojunction material prepared by the present invention can form a built-in electric field to maintain the electron transfer state after the charge distribution in the heterojunction is balanced under light excitation, thereby preventing electron-hole recombination and improving the photocatalytic performance.

[0032] (7) The Cu2S@COPs heterojunction material prepared by the present invention has good selectivity for photocatalytic reduction of U(VI).

[0033] (8) The Cu2S@COPs heterojunction material prepared by the present invention has strong photocatalytic reduction ability and high efficiency for U(VI), and is a highly efficient photocatalyst with good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0035] Figure 1 Schematic diagram of the synthesis process of Cu2S@COPs in Example 6 of the present invention (including the schematic diagram of the synthesis process of Cu2S in Example 2).

[0036] Figure 2 This is the SEM image of Cu2S in Example 2 of the present invention, wherein Figure b is an enlarged image of a single Cu2S nanosheet in Figure a.

[0037] Figure 3 This is the HRTEM image of Cu2S@COPs in Example 6 of the present invention, wherein Figure b is an enlarged image of the Cu2S@COPs heterojunction structure in Figure a.

[0038] Figure 4 1 and 2 are PXRD patterns of Cu2S in Example 2 and Cu2S@COPs in Example 6 of the present invention, wherein the vertical lines are standard PXRD card data of Cu2S.

[0039] Figure 5 FTIR graphs of Cu2S in Example 2 and Cu2S@COPs in Example 6 of the present invention.

[0040] Figure 6 These are the adsorption isotherms of the photocatalytic removal of uranium by Cu2S in Application Example 1 and Cu2S@COPs in Application Example 2 of the present invention.

[0041] Figure 7 These are the adsorption kinetics diagrams of the photocatalytic removal of uranium by Cu2S in Application Example 1 and Cu2S@COPs in Application Example 2 of the present invention.

[0042] Figure 8 This is the selectivity diagram of Cu2S@COPs for uranium in the presence of interfering ions in Application Example 2 of the present invention.

[0043] Fig. 9 This is the electron transfer pathway and photocatalytic reduction mechanism diagram of Cu2S@COPs in Application Example 2 of the present invention. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.

[0046] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.

[0047] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.

[0048] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.

[0049] The invention discloses a preparation method and application of a hexagonal Cu2S nanosheet and a Cu2S@COPs heterojunction material.

[0050] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0051] Example 1

[0052] A method for preparing a Cu2S nanosheet material with a hexagonal morphology comprises the following steps:

[0053] Copper chloride dihydrate (170 mg, 1 μmol) and oleylamine / octadecene (1:0.5, 10.0 mL) were mixed evenly and degassed for 30 min under nitrogen conditions, and stirred and heated to react under anaerobic conditions. When the temperature reached 130 ° C, 5 mL of tert-dodecyl mercaptan was injected, and then the temperature was continued to rise, and the reaction was carried out at 220 ° C for 30 min, and then 10 mL of ethanol was slowly injected to terminate the reaction, and then ultrasonically dispersed in n-hexane and precipitated in ethanol. The reaction solution was centrifuged (2000 rpm) for washing, and the obtained Cu2S was resuspended in n-hexane and dried at room temperature to obtain Cu2S nanosheets.

[0054] Example 2

[0055] A method for preparing a Cu2S nanosheet material with a hexagonal morphology comprises the following steps:

[0056] Copper chloride dihydrate (170 mg, 1 μmol) and oleylamine / octadecene (1:1, 10.0 mL) were mixed evenly and degassed for 30 min under nitrogen conditions, and stirred and heated to react under anaerobic conditions. When the temperature reached 130 ° C, 5 mL of tert-dodecyl mercaptan was injected, and then the temperature was continued to rise, and the reaction was carried out at 220 ° C for 30 min, and then 10 mL of ethanol was slowly injected to terminate the reaction, and then ultrasonically dispersed in n-hexane and precipitated in ethanol. The reaction solution was centrifuged (2000 rpm) for washing, and the obtained Cu2S was resuspended in n-hexane and dried at room temperature to obtain Cu2S nanosheets.

[0057] Example 3

[0058] A method for preparing a Cu2S nanosheet material with a hexagonal morphology comprises the following steps:

[0059] Copper chloride dihydrate (170 mg, 1 μmol) and oleylamine / octadecene (1:1.5, 10.0 mL) were mixed evenly and degassed for 30 min under nitrogen conditions, and stirred and heated under anaerobic conditions. When the temperature reached 130 ° C, 5 mL of tert-dodecyl mercaptan was injected, and then the temperature was continued to rise, and the reaction was carried out at 220 ° C for 30 min, and then 10 mL of ethanol was slowly injected to terminate the reaction, and then ultrasonically dispersed in n-hexane and precipitated in ethanol. The reaction solution was centrifuged (2000 rpm) for washing, and the obtained Cu2S was resuspended in n-hexane and dried at room temperature to obtain Cu2S nanosheets.

[0060] Example 4

[0061] A method for preparing a Cu2S nanosheet material with a hexagonal morphology comprises the following steps:

[0062] Copper chloride dihydrate (170 mg, 1 μmol) and oleylamine / octadecene (1:2, 10.0 mL) were mixed and degassed for 30 min under nitrogen conditions, and stirred and heated under anaerobic conditions. When the temperature reached 130 ° C, 5 mL of tert-dodecyl mercaptan was injected, and then the temperature was continued to rise, and the reaction was carried out at 220 ° C for 30 min, and then 10 mL of ethanol was slowly injected to terminate the reaction, and then ultrasonically dispersed in n-hexane and precipitated in ethanol. The reaction solution was centrifuged (2000 rpm) for washing, and the obtained Cu2S was resuspended in n-hexane and dried at room temperature to obtain Cu2S nanosheets.

[0063] Example 5

[0064] A method for preparing a Cu2S@COPs heterojunction material based on a click chemistry reaction specifically comprises the following steps:

[0065] Cu2S nanosheets (40 mg, 0.25 μmol) obtained in Example 2, 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine (32 mg, 0.084 μmol), 4,4'-bis(azidophenyl)-2,2'-disulfonic acid disodium tetrahydrate (55 mg, 0.126 μmol) and dimethyl sulfoxide / water (35:4, 78 mL) were mixed evenly, and the resulting reaction solution was reacted at 80°C for 12 h under stirring conditions. The solid was cooled and collected, and the Cu2S@COPs heterojunction material was obtained after washing and drying with acetone, methanol and dichloromethane by centrifugation (5000 rpm).

[0066] Example 6

[0067] A method for preparing a Cu2S@COPs heterojunction material based on a click chemistry reaction specifically comprises the following steps:

[0068] The Cu2S nanosheets (50 mg, 0.31 μmol) obtained in Example 2, 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine (32 mg, 0.084 μmol), 4,4'-bis(azidophenyl)-2,2'-disulfonic acid disodium tetrahydrate (55 mg, 0.126 μmol) and dimethyl sulfoxide / water (35:4, 78 mL) were mixed evenly, and the resulting reaction solution was reacted at 80°C for 12 h under stirring conditions. The solid was cooled and collected, and the Cu2S@COPs heterojunction material was obtained after washing and drying with acetone, methanol and dichloromethane by centrifugation (5000 rpm).

[0069] Example 7

[0070] A method for preparing a Cu2S@COPs heterojunction material based on a click chemistry reaction specifically comprises the following steps:

[0071] Cu2S nanosheets (60 mg, 0.38 μmol) obtained in Example 2, 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine (32 mg, 0.084 μmol), 4,4'-bis(azidophenyl)-2,2'-disulfonic acid disodium tetrahydrate (55 mg, 0.126 μmol) and dimethyl sulfoxide / water (35:4, 78 mL) were mixed evenly, and the resulting reaction solution was reacted at 80°C for 12 h under stirring conditions. The solid was cooled and collected, and the Cu2S@COPs heterojunction material was obtained after washing and drying with acetone, methanol and dichloromethane by centrifugation (5000 rpm).

[0072] In order to further demonstrate the beneficial effects of the present invention and to better understand the present invention, the following comparative examples and application examples are used to further illustrate the technical features of the device and its application disclosed in the present invention, but they should not be understood as limitations of the present invention. Other improvements made by those skilled in the art based on the above invention content without creative work are also considered to fall within the scope of protection of the present invention.

[0073] Comparative Example 1

[0074] Copper chloride dihydrate (170 mg, 1 μmol) and 10 mL of oleylamine were mixed and degassed for 30 min under nitrogen conditions, and stirred and heated under anaerobic conditions. When the temperature reached 130°C, 5 mL of tert-dodecyl mercaptan was injected, and then the temperature was continued to rise, and the reaction was carried out at 220°C for 30 min, and then 10 mL of ethanol was slowly injected to terminate the reaction, and then ultrasonically dispersed in n-hexane and precipitated in ethanol, the reaction solution was centrifuged (2000 rpm) for washing, and the obtained Cu2S was resuspended in n-hexane and dried at room temperature to obtain Cu2S nanosheets.

[0075] Comparative Example 2

[0076] Copper chloride dihydrate (170 mg, 1 μmol) and 10 mL of octadecene were mixed and degassed for 30 min under nitrogen conditions, and stirred and heated under anaerobic conditions. When the temperature reached 130°C, 5 mL of tert-dodecyl mercaptan was injected, and then the temperature was continued to rise, and the reaction was carried out at 220°C for 30 min, and then 10 mL of ethanol was slowly injected to terminate the reaction, and then ultrasonically dispersed in n-hexane and precipitated in ethanol, the reaction solution was centrifuged (2000 rpm) for washing, and the obtained Cu2S was resuspended in n-hexane and dried at room temperature to obtain Cu2S nanosheets.

[0077] Comparative Example 3

[0078] Cu2S nanosheets (60 mg, 0.38 μmol) obtained in Example 2, 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine (32 mg, 0.084 μmol), 4,4'-bis(azidophenyl)-2,2'-disulfonic acid disodium tetrahydrate (55 mg, 0.126 μmol) and 78 mL of dimethyl sulfoxide were mixed evenly, and the resulting reaction solution was reacted at 80°C for 12 h under stirring conditions. The solid was cooled and collected, and the Cu2S@COPs heterojunction material was obtained after washing and drying with acetone, methanol and dichloromethane by centrifugation (5000 rpm).

[0079] Comparative Example 4

[0080] Cu2S nanosheets (60 mg, 0.38 μmol) obtained in Example 2, 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine (32 mg, 0.084 μmol), 4,4'-bis(azidophenylethylene)-2,2'-disulfonic acid disodium tetrahydrate (55 mg, 0.126 μmol) and 78 mL of water were mixed evenly, and the resulting reaction solution was reacted at 80°C for 12 h under stirring conditions. The solid was cooled and collected, and the Cu2S@COPs heterojunction material was obtained after washing and drying with acetone, methanol and dichloromethane by centrifugation (5000 rpm).

[0081] Test Case

[0082] Figure 1 This is a schematic diagram of the synthesis process of Cu2S@COPs in Example 6 of the present invention, which includes the schematic diagram of the synthesis process of Cu2S in Example 2.

[0083] Figure 2 This is a SEM image of Cu2S in Example 2 of the present invention, wherein Figure b is an enlarged image of a single Cu2S nanosheet in Figure a. In the SEM image of Cu2S, the nanosheet exhibits a regular hexagonal morphology.

[0084] Figure 3 This is the HRTEM image of Cu2S@COPs in Example 6 of the present invention, where Figure b is an enlarged image of the Cu2S@COPs heterojunction structure in Figure a. In the HRTEM image of Cu2S@COPs, COPs are uniformly wrapped on the surface of Cu2S to form a core-shell heterostructure.

[0085] Figure 4 The PXRD patterns of Example 2 Cu2S and Example 6 Cu2S@COPs of the present invention are shown in Figure 1, where the vertical lines are the standard PXRD card data of Cu2S. The PXRD pattern of Cu2S is consistent with the standard card (PDF#46-1195), indicating that its crystallinity is good. After forming the Cu2S@COPs heterojunction material, the PXRD characteristics of Cu2S can also be maintained.

[0086] Figure 5 The FTIR spectra of Cu2S in Example 2 and Cu2S@COPs in Example 6 of the present invention are shown in Figure 1. In the FTIR spectra of Cu2S, a peak at 615 cm -1 The characteristic fingerprint corresponding to the metal sulfide is still retained after the formation of the Cu2S@COPs heterojunction. In the FTIR spectrum of Cu2S@COPs, the peak corresponding to the terminal alkynyl group of the monomer (3236cm -1 ) and the azido peak (2133 cm -1 ) disappears, and at 1506cm -1 The characteristic peaks of 1,2,3-triazole groups appeared at , indicating that COPs were successfully formed on Cu2S via click chemistry reaction.

[0087] Application Example 1

[0088] The Cu2S nanosheet material obtained in Example 2 is applied to the photocatalytic removal of radionuclide uranium, and the specific steps are as follows:

[0089] (1) Thermodynamics of photocatalytic removal of uranium by Cu2S nanosheets

[0090] Under dark conditions, 5 mg of Cu2S nanosheets were added to 20 mL of solutions with different concentrations of U(VI) (50, 100, 200, 300 and 400 mg / L). Then, 0.5 mL of the suspension was taken out and filtered through a 0.22 μm microporous membrane, and the remaining uranium concentration in the filtrate was measured by inductively coupled plasma mass spectrometry. Figure 6 The adsorption isotherms of Cu2S and Cu2S@COPs for the photocatalytic reduction of U(VI) under visible light irradiation. Without the addition of sacrificial agents, the photocatalytic removal capacity of Cu2S nanosheets and Cu2S@COPs heterojunction materials for U(VI) reached 558.9 mg g -1 and 1164.6 mg g -1 .

[0091] (2) Photocatalytic removal kinetics of uranium by Cu2S nanosheets

[0092] In the dark, 5 mg of Cu2S nanosheet material was added to 20 mL of a solution containing 500 mg / L U(VI). Then, under visible light irradiation, 0.5 mL of the suspension was taken out at regular intervals and filtered through a 0.22 μm microporous filter membrane. The remaining uranium concentration in the filtrate was measured by inductively coupled plasma mass spectrometry. Figure 7This is the adsorption kinetics diagram of the photocatalytic reduction of U(VI) by Cu2S and Cu2S@COPs under visible light irradiation. It can be seen that both Cu2S nanosheet materials and Cu2S@COPs heterojunction materials can achieve photocatalytic removal equilibrium of U(VI) in a short time.

[0093] Application Example 2

[0094] The Cu2S@COPs heterojunction material obtained in Example 6 is applied to the photocatalytic removal of uranium nuclides, and the specific steps are as follows:

[0095] (1) Thermodynamics of photocatalytic removal of uranium by Cu2S@COPs heterojunction materials

[0096] Under dark conditions, 5 mg of Cu2S@COPs heterojunction material was added to 20 mL of solutions with different concentrations of U(VI) (50, 100, 200, 300, 400 and 500 mg / L). Then, 0.5 mL of the suspension was taken out and filtered through a 0.22 μm microporous membrane, and the remaining uranium concentration in the filtrate was measured by inductively coupled plasma mass spectrometry. Figure 6 It is the adsorption isotherm diagram of the photocatalytic reduction of U(VI) by Cu2S and Cu2S@COPs under visible light irradiation.

[0097] (2) Photocatalytic removal kinetics of uranium nuclide by Cu2S@COPs heterojunction material

[0098] Under dark conditions, 5 mg of Cu2S@COPs heterojunction material was added to 20 mL of a solution containing 500 mg / L U(VI). Then, under UV / visible light irradiation, 0.5 mL of the suspension was taken out at regular intervals and filtered through a 0.22 μm microporous filter membrane. The remaining uranium concentration in the filtrate was measured by inductively coupled plasma mass spectrometry. Figure 7 This is the adsorption kinetics diagram of the photocatalytic reduction of U(VI) by Cu2S and Cu2S@COPs under visible light irradiation.

[0099] (3) Photocatalytic selectivity of Cu2S@COPs heterojunction materials for the removal of uranium

[0100] 5 mg of Cu2S@COPs heterojunction material was added into a 20 mL mixed solution containing 50 mg / L U(VI) and 250 mg / L interfering metal ions (Mg(II), Al(III), Ca(II), Co(II), Ni(II), Y(III), La(III), Ce(III), Pr(III), Nd(III), Sm(III), Eu(III), Gd(III), Tb(III), Dy(III), Ho(III), Er(III), Tm(III) and Lu(III)). The mixture was then irradiated under visible light for 3 h. 0.5 mL of the suspension was taken out and filtered through a 0.22 μm microporous filter membrane. The concentrations of various metal ions in the filtrate were measured by inductively coupled plasma mass spectrometry. Figure 8 This is the removal rate of different metal ions by Cu2S@COPs heterojunction under visible light irradiation. Figure 8 It can be seen that under the condition that the coexisting ion concentration is 5 times the uranium concentration, Cu2S@COPs still has high selectivity for U(VI). Even in the presence of multiple interfering ions, the removal efficiency of Cu2S@COPs heterojunction for U(VI) is still higher than 80%, showing good selectivity.

[0101] (4) Study on the photocatalytic removal mechanism of uranium nuclide by Cu2S@COPs heterojunction material

[0102] Fig. 9 This is the electron transfer path and photocatalytic reduction mechanism diagram of the Cu2S@COPs heterojunction. Under light conditions, photogenerated electrons are excited in the heterojunction material. Since Cu2S and COPs belong to type I heterojunction, photogenerated electrons are more likely to transfer from the conduction band of COPs to the conduction band of Cu2S, thereby promoting the separation of photogenerated electrons and holes and achieving efficient photocatalytic reduction of U(VI).

[0103] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a Cu2S nanosheet material having a hexagonal morphology, characterized in that: The specific steps include: The inorganic copper and the organic solvent are mixed evenly and then degassed under nitrogen conditions, and stirred and heated for reaction under anaerobic conditions; when the temperature reaches 120-140°C, organic sulfur is injected, and then the temperature is continuously raised, and the reaction is carried out at 180-220°C for 10-30 minutes, and then ethanol is slowly injected to terminate the reaction, and then the reaction solution is centrifuged and washed, and the obtained Cu2S is resuspended in n-hexane and dried at room temperature to obtain the Cu2S nanosheet material with hexagonal morphology.

2. The method for preparing the Cu2S nanosheet material having a hexagonal morphology according to claim 1, characterized in that: The inorganic copper is cupric chloride dihydrate, and the organic sulfur is tert-dodecyl mercaptan; and the amount ratio of the inorganic copper to the organic sulfur is 1-1.5 μmol: 2-5 mL.

3. The method for preparing the Cu2S nanosheet material having a hexagonal morphology according to claim 1, characterized in that: The organic solvent is a mixed solution of oleylamine and octadecene in a volume ratio of 1:(0.5-2); and the amount ratio of the inorganic copper to the organic solvent is 1-1.5 μmol:3-10 mL.

4. Use of the Cu2S nanosheet material with hexagonal morphology prepared by the method as claimed in claim 1 in photocatalytic removal of uranium nuclides.

5. A Cu2S@COPs heterojunction material, characterized in that: A covalent organic polymer heterostructure with triazole as a connecting structure is synthesized in situ by a click chemistry reaction of an alkynyl monomer and an azide monomer under the catalytic action of Cu2S prepared by the method as claimed in claim 1.

6. The Cu2S@COPs heterojunction material according to claim 5, characterized in that: The alkynyl monomer is 2,4,6-tris(4-ethynylphenyl)-1,3,5-triazine, and the azide monomer is 4,4'-bisazidostilbene-2,2'-disulfonic acid disodium tetrahydrate.

7. A method for preparing the Cu2S@COPs heterojunction material according to claim 5, characterized in that: The specific steps include: The Cu2S nanosheets, alkynyl monomers, azide monomers and solvent prepared by the method as claimed in claim 1 are mixed evenly, the obtained reaction solution is reacted at 70-120° C. for 12-24 hours under stirring conditions, the solid is collected by cooling, centrifugation, washing and drying to obtain the Cu2S@COPs heterojunction material.

8. The method for preparing the Cu2S@COPs heterojunction material according to claim 7, characterized in that: The ratio of the alkynyl monomer, the azide monomer, the Cu2S nanosheets and the solvent is (0.06-0.3 μmol): (0.1-0.5 μmol): (40-60 mg): (70-80 mL).

9. The method for preparing the Cu2S@COPs heterojunction material according to claim 8, characterized in that: The solvent is a mixed solution of water / dimethyl sulfoxide in a volume ratio of 1:(5-15).

10. Use of the Cu2S@COPs heterojunction material according to claim 5 or the Cu2S@COPs heterojunction material prepared by the method according to any one of claims 7 to 9 in photocatalytic removal of uranium nuclides.